Frequency of Factors Leading to Oligohydramnios in Patients Presenting to Women and Children Hospital, Dera Ismail Khan - Faryal Shah, Maria Ghafoor, Najma Bibi, Aimen Saleem, Rubina Babar, Abeela Azam (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of factors leading to oligohydramnios in patients presenting to women and children hospital, Dera Ismail Khan. Materials and methods: This cross sectional study was conducted in obstetrics and gynecology department, Women and children teaching hospital Dera Ismail khan from 1 August, 2020 to 31 January, 2021, comprising 185 patients. Sampling technique used was convenient non-probability sampling. Factors leading to oligohydramnios (Primigravida, history of abortion, gestational age > 40 weeks, history of UTI and history of high blood pressure) were noted as per operational definition and recorded on especially designed proforma. Result: A total of 185 pregnant women with oligohydramnios were included in the study. Factors leading to oligohydramnios (Primigravida, history of abortion, gestational age > 40 weeks, history of UTI and history of high blood pressure) were noted. Age range in this study was from 18 to 35 years with mean age of 27.178±2.39 years and mean weight was 68.908±3.82 Kg. Factors leading to oligohydramnios were, primigravida 34.1%, History of Abortion 27%, gestational age > 40 weeks 45.4%, history of UTI 15.7% and history of high blood pressure was 21.1%. Practical implication: This study will help the gynecologists in diagnosis and analysis of the oligohydramnios based on the risk factors discussed in this research. Conclusion: It can be concluded from our study that most common associated factors were primigravida, history of abortion, gestational age > 40 weeks, history of UTI and history of high blood pressure. Keywords: Amniotic fluid, Gestation, Hypertension, Pregnancy, Oligohydramnios, Primigravida.